Predictors of Vaccine Acceptance, Confidence, and Hesitancy in General, and COVID-19 Vaccination Refusal in the Province of Quebec, Canada - Nizigiyimana A; Acharya D; Morillon GF; Poder TG (Patient Preference and Adherence, 2022)
Alexis Nizigiyimana,1– 3,* Dilaram Acharya,1,4,* Gabin F Morillon,5,6 Thomas G Poder1,3,6 1Department of Management, Evaluation and Health Policy, School of Public Health, Université de Montréal, Montréal, QC, Canada; 2Centre de recherche en santé publique, Montréal, QC, Canada; 3Centre de Recherche de l’Institut Universitaire en Santé Mentale de Montréal, CIUSSS de l’Est-de-l’île-de-Montréal, Montréal, QC, Canada; 4Medical Affairs and Innovation, Héma-Québec, Montréal, QC, Canada; 5Faculté d’économie, Université de Montpellier, Montpellier, France; 6Centre interuniversitaire de recherche en analyse des organisations, Montréal, QC, Canada*These authors contributed equally to this workCorrespondence: Thomas G Poder, Department of management, evaluation and health policy, School of Public Health, Université de Montréal, Montréal, QC, Canada, Email thomas.poder@umontreal.caIntroduction: A surge of COVID-19 variants is a major concern, and literatures that support developing an optimum level of herd immunity are meaningful. This study aimed to examine the factors associated with vaccine acceptance, confidence, and hesitancy in general, and COVID-19 vaccination refusal in the general population of Quebec, Canada.Methods: A web-based cross-sectional survey was conducted in October and November 2020 among French-speaking participants above 18 years of age employing quota sampling technique. The questionnaire included socio-demographic and attitudinal variables towards vaccination. Logistic regression analyses were conducted to examine the association between independent and outcome variables.Results: Of total 1599 participants, 88.9%, 87.5%, 78.5%, and 18.2%, respectively, indicated vaccine acceptance, high level of vaccine confidence, low level of vaccine hesitancy, and COVID-19 vaccination refusals. Participants having higher education, income, and fear of COVID-19 (FCV-19S) were more likely to get vaccinated, while smokers were less likely to get vaccinated. Similarly, age groups (40– 59, and ≥ 60 years), higher education, income, permanent resident in Canada, country of parents from Canada, ever faced acute disease in the family, higher sense of coherence, and FCV-19S scores were predictors of high levels of vaccine confidence. Higher education, income, sense of coherence and FCV-19S scores, and higher health-related quality of life (CORE-6D) produced lower levels of vaccine hesitancy. Conversely, those acting as caretaker, other essential worker, smoker, and those with financial losses were more likely to have higher vaccine hesitancy. Additionally, ≥ 60 years of age, higher education and income, country of parents from Canada, higher scores of willingness to take risk and FCV-19S were less likely to have high level of COVID-19 vaccination refusal.Conclusion: Over three quarters of the participants indicated positive attitudes toward vaccination. Some socio-demographic and health-related quality of life factors were associated with the outcome variables, and these should be sought while designing interventions to improve COVID-19 vaccination rates.Keywords: COVID-19, behaviour, health determinants, infectious diseases, public health, vaccination